ON A RECORD OF THE SPINY LOBSTER PANULIRUS PENICILLATUS OLIVIER FROM MADRAS - Radhakrishnan, E V; Vijayakumaran, M; Hameed, K Shahul (Indian Journal of Fisheries, 2011)
The occurrence of the spiny lobster, Panulirus penicillatus off Madras is reported for the first time. Eight species of palinurid loteters, namely, Panulirus homarus (Linnaeus), P. omatus (Fabridus), P. paiyphagus (Herbst), P. txrsicolor (Latreille), P. longipes longipes (A. Milne Edwards), P. penicillatus (Olivier), Palinustus mossambicus (Barnard), and Puerulus sewelli (Ramadan) are recorded from Indian waters. While four spedes, P. homarus, P. omatus, P. polyphagus and the deep sea lobster, P. sewelli form fairly good fishery, P. versicolor, P. penicillatus, P. longipes longipes and P. mossambicus are caught in small numbers